80.9k views
1 vote
If F(x)=2^x +5x and g(x)=3x-5 find (f+g)(x)

User Mataniko
by
5.2k points

1 Answer

2 votes

Final answer:

The sum of the functions
F(x) = 2^x + 5x and g(x) = 3x - 5 is
(f+g)(x) = 2^x + 8x - 5, which is obtained by adding the corresponding elements of each function and combining like terms.

Step-by-step explanation:

The question asks for the sum of two functions, F(x) and g(x). In mathematical terms, (f+g)(x) means we have to add the functions F(x) and g(x) together. This is done by adding the corresponding elements of each function.

Here are the given functions:

F(x) = 2x + 5x

g(x) = 3x - 5

To find (f+g)(x), we combine them like this:

(f+g)(x) = F(x) + g(x) = (2x + 5x) + (3x - 5)

Now, we simply combine like terms:

(f+g)(x) = 2x + 5x + 3x - 5

(f+g)(x) = 2x + 8x - 5

This is the simplified form of the sum of the functions F(x) and g(x).

User Gabriel Burt
by
5.2k points